PERSONAL PROTECTIVE EQUIPMENT UTILIZATION IN CENTRAL STERILE SUPPLY DEPARTEMENT PKU MUHAMMADIYAH HOSPITAL SURAKARTA - Etika Marsita Dewi (Journal of Industrial Hygiene and Occupational Health, 2019)
Personal Protective Equipment (PPE) utilization are very effective in minimizing injuries and accident for healthcare workers. Due to high availability of potential hazard in Central Sterile Supply Departement (CSSD) PKU Muhammadiyah Surakarta hospital management decided PPE utilization as an obligation for all healthcare workers This study aim to analyze risk and hazard factor, PPE function and availability, and healthcare workers PPE utilization in CSSD unit based on goverment regulations. This study used observational method and describe PPE utilization and implementation in CSSD unit as a result. The result of this study is the biggest risk factor, which is biological hazard. CSSD unit already prepared PPE that suit the goverment regulations. PPE utilization still not yet fully implemented regarding to CSSD regulations. Conclusion from this study, in general, PPE utilization and implementation in CSSD unit is according to goverment regulation UU No.1 Tahun 1970 and Per 08/MEN/VII/2010 from Kemnakertrans.Keyword:  PPE implementation, PPE utilization